Relationship Between Contract Management And Staff Satisfaction In Hospitals Affiliated To Tehran University Of Medical Sciences - Mohammadali Zhirafa; Soodabeh Vatankhah; Seyed Hesam Seyedein (Tehran University of Medical Sciences, 2012)
Background and Aim: Staff satisfaction is one of the basic and important indicators for assessment of contract management. The aim of this study was to survey relationship between contract management and staff satisfaction in hospitals affiliated to the Tehran University of Medical Sciences in 2011. Materials and Methods: This research was a cross-sectional and descriptive study. Six hospitals which were deployed a contract management system in recent years were chosen. A questionnaire with Likert scale was designed to measure the satisfaction. One hundered and twenty three employees filled the questionnaire. The data analysis was performed using descriptive statistics and paired t test. Results: The average staff satisfaction score before implementing contract management system was 3/04(out of 5) and after implementation was 2/86. The correlation of satisfaction among workers before and after the out sourcing was significant(P<0/005). It was clear that satisfaction was reduced after the transfer. Conclusion: The average staff satisfaction score before implementing contract management system was 3/04(out of 5) and after implementation was 2/86. The correlation of satisfaction among workers before and after the out sourcing was significant(P<0/005). It was clear that satisfaction was reduced after the transfer.